THU0252 Decreased Expression of Immunoregulatory Protein Programmed Death Ligand-1 (PD-L1) in Systemic Lupus Erythematosus (SLE) Placenta. (15th July 2016) - Stevens, A.M.; Yuasa, M.; Deutsch, G.
Abstract : Background: The increased rates of preeclampsia, pre-term birth, and intra-uterine growth restriction in SLE pregnancy are only partially explained by the vascular effects of anti-phospholipid antibodies. SLE patients themselves are on average born preterm, suggesting a heritable defect in maternal-fetal tolerance. PD-L1 is one candidate gene, in that it has been implicated in the both autoimmunity and maternal-fetal tolerance: PD-L1 is expressed on healthy antigen presenting cells to downregulate inflammatory responses, and also on placental trophoblasts at the maternal-fetal interface, where it inhibits alloreactive T cells. Peripheral blood antigen presenting cells from SLE patients are deficient in PD-L1 expression compared to remission or healthy controls. Little is known about placental costimulatory molecules in women with autoimmune diseases. Objectives: This study tested the hypothesis that placental PD-L1 expression is abnormally regulated in SLE pregnancy. Methods: Expression of PD-L1 was quantified by immunohistochemistry in placentas from 6 SLE patients, 7 rheumatoid arthritis patients (RA) and 9 healthy control women obtained from the Global Alliance for the Prevention of Prematurity and Stillbirth Repository. PD-L1 mRNA expression was assayed by RT-PCR and normalized to GAPDH expression. PD-L1 on peripheral CD14+/CD11c+ monocytes was assayed by flow cytometry. Significant differences between groups were tested by T-test. Results: By immunostaining, PD-L1 expression in SLE placentas was low compared to control groups. PD-L1 mRNA expression correlated with protein expression, although the differences were not significant. A limited analysis of CD45 and CD43 co-expression suggested that a subset of maternal T lymphocytes expressed PDL-1 but that fetal cells did not. The mean gestational age was lower in SLE (27 weeks, range 18–39) compared to RA (38, range 29–40) and controls (34, range 19–40), but there was not a strong correlation between gestational age and PD-L1 expression (R 2 0.18). Three SLE patients exhibited placental insufficiency, with relatively low PD-L1 expression (18 compared to 24 in healthy SLE). On peripheral blood monocytes, PD-L1 expression was low in juvenile SLE patients compared to healthy controls (55% of SLE monocytes v. 93% of healthy monocytes, p=0.001). Although in the normal range, mothers of SLE patients also had relatively low PD-L1 expression compared to control mothers (87% v. 94%, p=0.04). Conclusions: Placental PD-L1 expression is dysregulated in women with SLE. Inadequate expression of PDL-1 in the placentas of patients with SLE could result in loss of maternal-fetal tolerance, contributing to the high rate of pregnancy complications in SLE. Disclosure of Interest: None declared